Enhancement in photovoltaic performance of CZTS Thin-film solar cells through varying stacking order and sulfurization time - Olgar, M. A. (Journal of materials science. Materials in electronics, 2022)
The CZTS samples were produced by a two-stage method, which includes deposition of Cu, Sn, Zn, and ZnS layers using magnetron sputtering to obtain CuSn/Zn/Cu and CuSn/ZnS/Cu stacks. The latter stage involves the sulfurization process of stacked films at 550 °C for varied sulfurization time (60, 90, 120, and 150 s) employing Rapid Thermal Processing (RTP) method to attain CZTS structure. The prepared CZTS thin films were analyzed utilizing several characterization methods. The energy-dispersive X-ray spectroscopy (EDX) measurements revealed that all sulfurized samples had Cu-poor and Zn-rich chemical composition. All samples showed that diffraction peaks belonged to pure kesterite CZTS phase subject to their XRD patterns. Besides, it was observed that the sulfurization time had a crucial effect on the crystal size of the samples. The Raman spectra of the samples verified the constitution of kesterite CZTS phase and it provides detection of some CTS-based secondary phases. The scanning electron microscopy (SEM) image of the films revealed that polycrystalline surface structures were observable in all the samples. However, plate-like surface features were observed in some samples that may refer to CTS-based secondary phases depending on chemical composition. From 1.40 to 1.48 eV optical band gap values were obtained from ( αhν ) 2 vs. photon energy ( hν ) plots. The Van der Pauw measurements exhibited that the CZTS samples produced employing CuSn/ZnS/Cu stack had lower resistivity (~ 10 –3 Ω cm), higher carrier concentration values (~ 10 21 cm −3 ), and higher charge mobility. The solar cells prepared using the most promising CZTS samples employing CuSn/Zn/Cu and CuSn/ZnS/Cu precursor films revealed 1.95% and 3.10% conversion efficiencies, respectively.